Fermentation of lupin with lactic acid bacteria using a bioreactor - Nikola, Malviina (My University, 2024)
The rising interest in incorporating lupin into our diet is driven by its unique nutritional value, notably its high protein content, coupled with its sustainability. Fermentation is a natural bioprocess widely employed to enhance shelf life and microbiological safety. Lactic acid bacteria fermentation, that involves the production of lactic acid from glucose, has shown promise for usage in plant-based foods. The aim of this project is to examine the effect of lactic acid bacteria fermentation on dairy analogue made from lupin flour. Lupin flour was mixed with tap water using a blender and liquid fraction was separated from solids by centrifugation. Fermentation was tested with three Lactiplantibacillus plantarum strains for 72 h at 30 °C. Final fermentations using a bioreactor was done for 24 h at 28 °C. Samples were taken out at the different timepoints, and pH was measured through fermentation process. Simple sugars and organic acids were analysed quantitively using gas chromatography with flame ionization detector. The results indicated the success of the fermentation process, with sugars being converted into lactic acid. Noteworthy findings revealed no significant differences among the employed bacterial strains, except for distinct effects observed in citric acid levels.
Keywords: bioreactor, fermentation, GC-FID, lactic acid bacteria, lupin